Dragonfly eyes - Cao, Wenxuan, 1954- (Candlewick Press, 2022)
Du Meixi and his French wife Océane have built a silk empire that has afforded them a privileged life in the early twentieth century Shanghi. During the following years, Océane develops a special bond with her youngest grandchild Ah-Mei, who looks like her and knows her as Nainai. Through war and the events of the Cultural Revolution, Nainai and her family suffer persecution and lose their business, leaving their family with only their bond and personal strength to sustain them.